2023
DOI: 10.1039/d3ja00060e
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced breakdown spectroscopy and stoichiometry to identify various types of defects in metal-additive manufacturing parts

Abstract: Various defects of additive manufacturing (AM) components seriously impact their performance, which restricts the industry’s development process. Therefore, component defects should be classified quickly and treated in different ways. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The importance of the features recorded by the RF classifier showed that the spectral intensity of Fe i 414.234 nm and Al i 396.054 nm and the spectral kurtosis in the wavelength range of 484–490 nm and 508–518 nm were the most effective features for porosity identification. Yang et al 20,21 used LIBS technology combined with four classifiers, naive Bayes (NB), k -nearest neighbor, decision tree and RF, to classify and identify defective and non-defective samples of AM parts. The results showed that the RF model had the best recognition effect.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the features recorded by the RF classifier showed that the spectral intensity of Fe i 414.234 nm and Al i 396.054 nm and the spectral kurtosis in the wavelength range of 484–490 nm and 508–518 nm were the most effective features for porosity identification. Yang et al 20,21 used LIBS technology combined with four classifiers, naive Bayes (NB), k -nearest neighbor, decision tree and RF, to classify and identify defective and non-defective samples of AM parts. The results showed that the RF model had the best recognition effect.…”
Section: Introductionmentioning
confidence: 99%